The Acceptance of E-Commerce Among SMEs Entrepreneurs in Northern Area of Kedah Darul Aman State - Mahamud, Ariffin (2003)
The purpose of this research was to find out the statistics of the acceptance of e-commerce amongst Small and Medium Sized entrepreneurs in Northern Area of Kedah Darul Aman State. This study focuses only on entrepreneurs that are registered with the government agency that is responsible to their development. A total of 628 SMEs entrepreneurs that are registered under the government agency were taken as respondents. Data and Information were gathered using questionnaires as an instrument, and analysed using SPSS statistical package. The findings show that nearly 50% of the respondents used personal computer (PC) in their business activities. Out of this, almost 10% of them had informational websites which merely display information regarding their business without offering any online transaction facilities. These findings show that the level of e-commerce acceptance amongst SMEs entrepreneurs was still at the early stage. Hopefully, the findings could assist the hindering factors and the problems that arise in using Information and Communication Technology, especially in e-commerce among SMEs entrepreneurs, so that they will be competitive in the global market.